2013
DOI: 10.1155/2013/932472
|View full text |Cite
|
Sign up to set email alerts
|

Thiol Redox Sensitivity of Two Key Enzymes of Heme Biosynthesis and Pentose Phosphate Pathways: Uroporphyrinogen Decarboxylase and Transketolase

Abstract: Uroporphyrinogen decarboxylase (Hem12p) and transketolase (Tkl1p) are key mediators of two critical processes within the cell, heme biosynthesis, and the nonoxidative part of the pentose phosphate pathway (PPP). The redox properties of both Hem12p and Tkl1p from Saccharomyces cerevisiae were investigated using proteomic techniques (SRM and label-free quantification) and biochemical assays in cell extracts and in vitro with recombinant proteins. The in vivo analysis revealed an increase in oxidized Cys-peptides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…6A, B) supported the reduction in structural proteins MBP and CX32 (MYP0) in Sod1 -/mice shown in Figure 2C-E. Significant changes were also detected in redox-regulated proteins, including PRDX 5 and thioredoxin reductase 1 (TRXR1), but also metabolic enzymes known to be redox regulated (14,33,35,62) including transketolase (TKT), isocitrate dehydrogenase (IDH3A), electron transport flavoprotein subunit alpha (ETFA), and the cytoskeletal regulator gelsolin (GELS) (Fig. 6A) were downregulated in SN of the Sod1 -/model.…”
Section: Cuznsod Removal Induces Myofiber Atrophy and Oxidative Damagsupporting
confidence: 60%
See 1 more Smart Citation
“…6A, B) supported the reduction in structural proteins MBP and CX32 (MYP0) in Sod1 -/mice shown in Figure 2C-E. Significant changes were also detected in redox-regulated proteins, including PRDX 5 and thioredoxin reductase 1 (TRXR1), but also metabolic enzymes known to be redox regulated (14,33,35,62) including transketolase (TKT), isocitrate dehydrogenase (IDH3A), electron transport flavoprotein subunit alpha (ETFA), and the cytoskeletal regulator gelsolin (GELS) (Fig. 6A) were downregulated in SN of the Sod1 -/model.…”
Section: Cuznsod Removal Induces Myofiber Atrophy and Oxidative Damagsupporting
confidence: 60%
“…Proteomic analyses conducted in this study revealed an altered proteome in peripheral nerve of Sod1 -/mice, associated with downregulation of a number of metabolic enzymes that appear to be redox mediated (14,33,35,62). Overall, the data presented in this study indicate that despite the observed PNS degeneration in Sod1 -/mice, peripheral nerve of this model does not exhibit altered redox homeostasis similar to that seen in the skeletal muscle that it innervates but an altered proteome and specific changes in key regulatory redox Cys residues.…”
Section: Discussionmentioning
confidence: 64%
“…It's up-regulation in NOS3 overexpressing cells ( Fig. 1 D) could be counterbalanced by inactivation through thiol oxidation [48] as shown in Fig. 4 B.…”
Section: Discussionmentioning
confidence: 93%
“…The first studies of the Agarwal et al and Huang et al highlighted that the inhibition of heme biosynthesis could be the principal mechanism of action of sampangine [133,146]. Heme is present in complexes III and IV of the electron transport chain and possibly affects the heme dysfunction in sampangine-induced ROS production, as iron and various heme biosynthetic intermediates are known to be oxidized via reaction with cellular ROS [147][148][149][150].…”
Section: Sampangine Derivativesmentioning
confidence: 99%